Pengaruh Penambahan Tepung Kacang Merah Terhadap Daya Terima, Kadar Protein, dan Kadar Serat pada Bakso Jantung Pisang (Addition Effect of Red Beans Flour to the Acceptability, Protein Content, and Dietary Fiber of Banana Blossoms Meatballs) - Anita Kurnianingtyas; Ninna Rohmawati; Andrei Ramani (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Malnutrition is one of the nutritional problems caused by many factors. One contributing factor is the availability of food. The solution offered is diversification. The purpose of this study was to analyze the effect of adding red bean flour to the acceptability, protein content, and dietary fiber on the banana blossoms meatball. This study was a quasi experimental study. The sample was 25 panelist. Data were analyzed by using the power received Friedman test and Wilcoxon Sign Rank Test, protein content were tested using One Way ANOVA test, and dietary fiber were tested using the Kruskal-Wallis test and Mann Whitney test with a confidence level of 5% (α = 0,05). Based on the results of Friedman test acceptability flavor and color have a p value > α (0,05) so there was no significant difference between the addition of various proportions of red bean flour with the taste and color acceptance in banana blossoms meatballs. Acceptance smell texture has p value < α (0,05) so there was a significant difference between the addition of various proportions of red bean flour with the taste and color acceptance in meatball banana. The result of the protein content and fiber content indicates p value < α (0,05) so there was a significant difference between the addition of various proportions of red bean flour with protein content and fiber content on the banana blossoms meatballs. Keyword: Red Beans Fluor, Banana Meatballs, acceptability, protein, and dietary fiber